2001
DOI: 10.1002/jbm.1263
|View full text |Cite
|
Sign up to set email alerts
|

Effects on articular cartilage of subchondral replacement with polymethylmethacrylate and calcium phosphate cement

Abstract: Bone defects were created in rabbit medial femoral condyle in a model where subchondral bone was completely removed or about 2 mm of subchondral bone was maintained. Groups without augmentation and augmented with autogenous bone, polymethylmethacrylate, or calcium phosphate cement were sacrificed at 3, 12, and 24 weeks for evaluation of articular cartilage and observation of bone formation. In the model in which subchondral bone was completely removed, collapse of the subchondral bone together with exfoliation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 21 publications
0
30
1
2
Order By: Relevance
“…It has to be noticed that a subchondral presence of the PMMA could possibly influence the overlying cartilage. 44 We did not find any correlation with the amount of injected cement and pain or mobility at follow-up. Due to an exothermic reaction during PMMA cement polymerisation, it is suspected that local bone damage may be induced.…”
Section: Discussioncontrasting
confidence: 58%
“…It has to be noticed that a subchondral presence of the PMMA could possibly influence the overlying cartilage. 44 We did not find any correlation with the amount of injected cement and pain or mobility at follow-up. Due to an exothermic reaction during PMMA cement polymerisation, it is suspected that local bone damage may be induced.…”
Section: Discussioncontrasting
confidence: 58%
“…Combined anterior/posterior approaches are major surgical undertakings for the patient and do not seem to provide any real advantages over the anterior procedure alone [9,[14][15][16]. Transpedicular spongiosaplasty, in which autologous bone grafts are impacted in the vertebral body through the pedicles after reduction to increase the stiffness of the anterior column, was developed and promoted by Daniaux in 1986 as an interesting addition to posterior surgery [17]. Recent studies have shown that this technique does not prevent the recurrence of kyphosis reliably and reproducibly [5,18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that thermal damage from PMMA can contribute to postoperative degenerative changes [8,16,22,23,25,30]. When used in conjunction with PMMA, bone graft increases the distance between the exothermic reaction of PMMA and the articular cartilage, which may protect against thermal injury [3,13,21,23]. Wilkins et al suggested irrigation of the periarticular area with chilled saline as the cement cures as a method of prevention from heat necrosis [33].…”
Section: Discussionmentioning
confidence: 99%
“…PMMA has a modulus that is between cortical bone and cancellous bone and well above articular cartilage. PMMA acts as a rigid surface, concentrating pressure on the already thin cartilage and subchondral plate tissue [13,15,24]. This may result in cartilage damage, fracture, and arthrosis [13,15,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation